Logistical Simulation for Blending of Concrete Waste in Kori-1 NPP Decommissioning - Eui-Taek Lee; Chang-Lak Kim (Science and Technology of Nuclear Installations)
The Kori-1 nuclear power plant (NPP) decommissioning, South Korea’s first large-scale nuclear decommissioning project, presents challenges in managing radioactive bioshield concrete waste among others. While there has been considerable interest in decommissioning concrete waste in recent decades, most studies have focused primarily on the separation of contaminated concrete. This study extended previous research by evaluating the potential of blending methodologies for managing activated cement paste. Blending involves mixing radioactive waste with varying levels of radioactivity to achieve a more uniform concentration. This process may include combining low-level waste (LLW) with very LLW (VLLW), potentially allowing the mixture to be reclassified as VLLW. Separate blending models were developed using FlexSim software, modifying an existing model from a prior study. The simulations incorporated realistic industrial machinery settings and assumed that radionuclides were primarily concentrated in the porous cement paste. The results demonstrated that the cycle times were relatively short, with the addition of a blending process having minimal or negligible impact on the overall project schedule. These findings suggest that blending is feasible for large-scale application in nuclear decommissioning projects. Accordingly, this study provides a foundational framework for innovative waste management strategies in future decommissioning efforts.